Mathematical Models for the Representation of Some Physiological and Quality Changes during Fruit Storage - Castellanos, Diego Alberto; Herrera, Aníbal Orlando (Journal of Postharvest Technology, 2014)
In fruits and vegetables, certain physiological processes, such as respiration and transpiration, and quality properties, such as color, firmness or weight, are used as consumer-based criteria of acceptability and shelf-life indicators. Changes in the rates of oxygen consumption, carbon dioxide and water vapor generation and product quality properties result from a series of biochemical processes. These processes are affected by internal conditions such as the ripening state and by external conditions such as temperature or environmental gas concentration. Understanding the time-progress of these processes and properties, according to variables that affect the product, and the mathematical models that regulate them, would be beneficial in selecting the most appropriate storage and preservation conditions to meet determined quality and shelf-life requirements. This manuscript describes the effect of postharvest storage conditions on biochemical and physiological processes related to respiration and transpiration and on quality property changes. Moreover, equations developed by many authors that describe the changes in these processes and properties according to storage conditions are reported.